O documentário contemporâneo da Paraíba e as políticas públicas de incentivo à produção audiovisual - Gama, Filipe Brito (2013)
The present dissertation aims to study the relation between the production of documentaries in Paraíba in the first decade of the 2000s and public policies of incentive of audiovisual production. To understand this context, were observed what the main laws, edicts and contests that promote the financing of documentaries in Paraíba in the period surveyed, noting funding sources at the federal, state and municipal levels.During the research, was possible to map 25 documentary films made in Paraíba, funded by public edicts, which were analyzed separately and then compared in order to understand what are the main characteristics of this group of films. For the realization of this survey, we used the bibliography about audiovisual policy in Brazil, as well as texts about the national and Paraíba s documentary production. Additionally, was looked up to the texts of laws and edicts, and data offered by public agencies. The contact with the filmmakers and with the works were shaped as fundamental sources for realization of this text.